Penyuluhan Hukum Tentang Memahami Kewajiban Pelaku Usaha Terhadap Konsumen Dalam Mendukung Kepatuhan Regulasi di Desa Kutasari Kecamatan Kutasari Kabupaten Purbalingga. - Wiwin Muchtar Wiyono; Aris Priyadi; Prosawita Ririh Kusumasari (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract . Legal education is one way to improve public understanding of business actors' obligations to consumers, particularly in supporting compliance with applicable regulations. This study was conducted in Kutasari Village, Kutasari District, Purbalingga Regency, focusing on the legal education process for local businesses. The aim of this education was to increase business actors' awareness and knowledge of their rights and obligations, as well as the importance of complying with consumer regulations to create a fair and sustainable market. The methods used included focus group discussions and direct training involving legal experts and regulators. The results of the education showed a significant increase in business actors' understanding of their obligations, which is expected to have a positive impact on regulatory compliance at the local level. This legal education emphasized the importance of an educational approach in efforts to improve legal compliance and foster better relationships between businesses and consumers in the community. Keywords: Legal education, businesses, consumers, regulatory compliance, Kutasari Village, Purbalingga.